Unusual focal keratin expression in plexiform angiomyxoid myofibroblastic tumor: A case report and review of the literature. Issue 28 (July 2016) - Quero, Giuseppe; Musarra, Teresa; Carrato, Alfredo; Fici, Michelangelo; Martini, Maurizio; Dei Tos, Angelo Paolo; Alfieri, Sergio; Ricci, Riccardo
Abstract: Background: Plexiform angiomyxoid myofibroblastic tumor (PAMT), also known as plexiform fibromyxoma, is a rare distinctive benign intramural tumor, typical of gastric antrum, commonly causing mucosal ulceration with upper gastrointestinal bleeding and anemia, effectively treated by complete surgical resection usually accomplished by distal gastrectomy. Methods and Results: We herein report a 47-year-old man presenting with a syncopal episode, regurgitation and epigastric discomfort, bearing a gastric antral myxoid plexiform tumor positive for α-smooth muscle actin, vimentin and, partially, for caldesmon, desmin, and CD10; CD117, DOG1, CD34, S100, CAM5.2, CK20, CK7, EMA, p53, CDX2, chromogranin A, synaptophysin, anaplastic lymphoma kinase, Melan-A, and HMB-45 were all negative. All these features are typical of PAMT. Of note, focal positivity for AE1/AE3 and pan-CK KL1 was also present. Conclusions: The finding of a focal keratin expression in PAMT contributes to enlarge the immunophenotypic spectrum of this tumor type and is relevant for avoiding presurgical misdiagnoses which could ultimately lead to inappropriate overtreatment of patients with PAMT.